2003
DOI: 10.1074/jbc.m212978200
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Interleukin-12 in the Regulation of T Cell Plasma Membrane Compartmentation

Abstract: The immunological synapse initiates the clustering and stabilization of the T cell receptor by the formation of a large lipid microdomain that accumulates (e.g. CD4/ CD8) and segregates (e.g. CD45 and LFA-1) some proteins of the T cell plasma membrane. This work shows that a fraction of transmembrane glycoproteins CD26 and CD45 (the R0 isoform in particular) is present in the rafts of fresh and activated human T lymphocytes. CD26 is proposed as the costimulator of TCR-dependent activation, and CD45 is essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 65 publications
2
31
0
Order By: Relevance
“…DPP4/ CD26 is involved in T cell activation, T cell signalling and T cell differentiation due to its interactions with ADA, CD45, caveolin-1, CARMA-1 and M6P/IGFII-R [9]. These processes are regulated by the cytokines IL-2, IL-6, IL-10, IL-12, IL-17, IL-29, IFN-g and TGF-b, as well as compartmentation of DPP4/CD26 to either lipid rafts or internalization [8,9,48,88,89,[91][92][93]. Furthermore, post-translation modification of DPP4/CD26 such as sialylation also appears to influence compartmentation and/or the interactions with its binding partners [9,86,87,90].…”
Section: Dash Proteins In Immune Cellsmentioning
confidence: 99%
“…DPP4/ CD26 is involved in T cell activation, T cell signalling and T cell differentiation due to its interactions with ADA, CD45, caveolin-1, CARMA-1 and M6P/IGFII-R [9]. These processes are regulated by the cytokines IL-2, IL-6, IL-10, IL-12, IL-17, IL-29, IFN-g and TGF-b, as well as compartmentation of DPP4/CD26 to either lipid rafts or internalization [8,9,48,88,89,[91][92][93]. Furthermore, post-translation modification of DPP4/CD26 such as sialylation also appears to influence compartmentation and/or the interactions with its binding partners [9,86,87,90].…”
Section: Dash Proteins In Immune Cellsmentioning
confidence: 99%
“…The behavior of CXCR4 appears more complex because it can be found within both coated pits (Signoret et al, 1997) and detergentresistant plasma membrane domains (rafts; Nguyen and Taub, 2002). A fraction of cell-surface CD26 is also found within rafts (Salgado et al, 2003). Because a raft-mediated, clathrin-independent endocytosis pathway exists in T lym- phocytes (Lamaze et al, 2001), the identified receptors could drive Tat endocytosis through either a clathrin-dependent or a raft-mediated pathway, and the initial Tat uptake pathway in T cells remains to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…CD26 can act in three ways; through its binding to the ADA ectoenzyme (in humans and other mammals but not in mice), through its enzymatic activity, and through other transient protein-protein interactions (Fleischer, 1994;Franco et al, 1998;Morimoto and Schlossman, 1998;De Meester et al, 1999;Hildebrandt et al, 2000). Focusing on the T cells, complexity increases when we look at its regulation, since CD26 gene expression is both developmentally regulated and inducible following T cell activation, particularly when observed at the posttranslational level (translocation to the cell surface and glycosylation) (Hafler et al, 1986;Morimoto et al, 1989;Dang et al, 1991;Mattern et al, 1995;Amlot et al, 1996;Cordero et al, 1997;Yawalkar et al, 2000;Salgado et al, 2000Salgado et al, , 2003Boonacker et al, 2002).…”
Section: Article In Pressmentioning
confidence: 99%
“…We previously described the anti-CD26 mAb TA1/16 (Salgado et al, 2000(Salgado et al, , 2003 and recently used this mAb to further subdivide CD4 T cells as follows (unpublished data): CD45R0 bright CD26 + T cells (which included a very small CD26 bright population), CD45R0 weak CD26 + , CD45R0 À CD26 + and CD45R0 À CD26 À populations. CD26 was expressed on the whole population of CD4 + CD8 + medullary thymocytes and highly expressed (90% were CD26 + ) on human cord blood T cells (which were almost entirely CD45RA + ).…”
Section: Introductionmentioning
confidence: 99%